Hydrodeoxygenation of gas-phase vanillin biomass model compound into guaiacol over Pd/CeO2 catalyst - Ahmad Yaghi; Labeeb Ali; Toyin Shittu; Abbas Khaleel; Mohammednoor Altarawneh (Case Studies in Chemical and Environmental Engineering)
Vanillin (4-hydroxy-3-methoxybenzaldehyde) is an important platform chemical compound that is invariably produced from pyrolysis of various categories of biomass. Hydrodeoxygenation (HDO) of vanillin has been a thematic topic in catalysis with the underlying aim to devise processes and reactions for catalytic upgrading of bio-oil and in the production of value-added products. Herein, we investigate the HDO of an evaporated stream of vanillin over a 4 % load of palladium supported on ceria; a Pd/CeO2 catalyst. The synthesized catalyst was characterized by various techniques including XRD, XPS, EDX-SEM, HR-TEM, and TPR. The HDO reaction (carried out at temperatures from 100 °C to 300 °C at 10 °C/min ramp rate with a 5 % H2 feed ratio) resulted in a 95 % conversion of vanillin with an 85 % yield of guaiacol (2-methoxyphenol). Minute loads of alkylbenzene compounds (mainly xylene and ethylbenzene) also emerged. DFT computations elucidate pathways for the observed formation of guaiacol where synergistic effects of both Pd and vacant oxygen sites are highlighted. Overall, we presented a viable HDO route for an oxygenated biomass model compound at mild operational conditions (intermediate temperatures, ambient pressure, and moderate H2/Feed ratio).